CAMPUS MOSQUE–BASED ISLAMIC THERAPEUTIC COMMUNICATION FOR SPIRITUAL DEVELOPMENT AND SEXUAL HARASSMENT PREVENTION IN HIGHER EDUCATION: A CONCEPTUAL FRAMEWORK - Ari Oldwin Sitorus; Zainun; Winda Kustiawan (J-MD Jurnal Manajemen Dakwah, 2026)
This study aims to analyze and construct a conceptual model of Islamic therapeutic communication based in campus mosques for spiritual development as a preventive strategy against sexual violence in higher education institutions. This research employs a qualitative approach with a library research design. Data were collected through document analysis of academic journals, books, and relevant regulations, and were analyzed using thematic analysis consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The theoretical framework includes Michel Foucault’s theory of power relations, Johan Galtung’s violence triangle theory strengthened by contemporary feminism, Islamic therapeutic communication theory, and the concepts of zawajir and jawabir in Islamic criminal law. The findings indicate that sexual violence in higher education is a multidimensional phenomenon influenced by power asymmetry, patriarchal culture, and weak institutional protection systems. The discussion reveals that Islamic therapeutic communication through istima’, hiwar, and irsyad provides a transformative space for psychological and spiritual recovery as well as prevention. The integration of the four perspectives produces a mosque-based preventive model emphasizing power deconstruction, cultural transformation, therapeutic communication strengthening, and continuous internalization of Islamic values within academic environments.